UJI SEDUHAN DAUN TEH HIJAU (Camelia sinensis L.) PADA GINJAL MENCIT YANG DIBERI MONOSODIUM GLUTAMAT (MSG) - Reza Anindita (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2019)
ABSTRACTThis research aims to test the potential of green tea in the mice that are given byMSG. Duration of research is 30 days using animal test mice male strainsBALB/C. This study uses a complete randomized draft (RAL) factorial. Eachtreatment consists of P0 as a control given akuades 0.5 ml/w/day, P1 that wasgiven green tea 0.015 gr/bb/day, P2 that were given MSG 0.84 gr/w/day, P3which was given MSG 0.84 gr/w/day and Green tea 0.015 gr/bb/hr. Resultsshowed that the treatment of MSG doses 0.084 gr/w/day is capable of lose renal weight and increasing glomerular diameter and proximal tubule. Treatment ofbrewing green tea leaves a dose of 0.015 gr/w/day in mice that are given MSG orwithout being given the treatment of MSG able to increase renal weight and lowerglomerular diameter and proximal tubule. Statistical analysis showed nosignificant difference (P > 0.05) in the kidneys that was given the brew of greentea leaves in mice that were given MSG or without without being given MSGtreatment. The conclusion in this study is the treatment of brewing tea leavesGreen dose 0.015 gr/bb/hr is able to reduce the degeneration of renal tissue thatis given MSG dose 0.084 gr/bb/hr. Keywords: green tea, MSG, proximal tubule, glomerular and kidney